Association of statin and/or renin-angiotensin-aldosterone system modulating therapy with mortality in adults with diabetes admitted to hospital with COVID-19: A retrospective multicentre European study. Issue 5 (May 2022) - Harris, Sophie; Ruan, Yue; Wild, Sarah H.; Wargny, Matthieu; Hadjadj, Samy; Delasalle, Béatrice; Saignes, Maëva; Ryder, Robert EJ.; Field, Benjamin C.T.; Narendran, Parth; Zaccardi, Francesco; Wilmot, Emma G.; et al.
Abstract: Background & aims: To assess the impact of pre-admission renin-angiotensin-aldosterone system inhibitor (RAASi) and statin use on mortality following COVID-19 hospitalization in adults with pre-existing diabetes. Methods: Retrospective cohort study of adults with diabetes admitted to ninety-nine participating hospitals in the United Kingdom, France and Spain during the first wave of the COVID-19 pandemic. Logistic regression models adjusted for demographic factors and comorbidity were used to describe associations with mortality in hospital or within 28 days of admission and individual or combined RAASi and statin therapy prescription followed by a country level meta-analysis. Results: Complete data were available for 3474 (42.6%) individuals. Prescribing patterns varied by country: 25–50% neither RAASi nor statin therapy, 14–36% both RAASi and statin therapy, 9–24% RAASi therapy alone, 12–36% statin alone. Overall, 20–37% of patients died within 28 days. Meta-analysis found no evidence of an association between mortality and prescription of RAASi therapy (OR 1.09, CI 0.78–1.52 (I 2 22.2%)), statin (OR 0.97, CI 0.59–1.61 (I 2 72.9%)) or both (OR 1.14, CI 0.67–1.92 (I 2 78.3%)) compared to those prescribed neither drug class. Conclusions: This large multicentre, multinational study found no evidence of an association between mortality from COVID-19 infection in people with diabetes and use of either RAASi, statin or combination therapy. This provides reassurance that clinicians should not change their RAASi and statin therapy prescribing practice in people with diabetes during the COVID-19 pandemic. Highlights: No association between mortality from COVID-19 and renin-angiotensin-aldosterone system inhibitor or statin therapy. There was no evidence of an association dependent on ethnicity or type of diabetes. Significant international variation in renin-angiotensin-aldosterone system inhibitor and statin use. Reassurance to continue prescribing both therapies throughout the pandemic.